The Compatibility Analysis of Serum Ascites Albumin Gradient and Ascitic Fluid Evaluation to Clinical Diagnosis of the Patient - Ivonne Desiana Thioritz; Yuyun Widaningsih; Fitriani Mangarengi (Indonesian Association of Clinical Pathologist and Medical laboratory, 2019)
Ascites is a condition of abnormal fluid accumulation in the peritoneal cavity that can be caused by many underlying diseases. Some studies conclude that ascitic fluid evaluation with transudate-exudate concept has been replaced by greater indicator, known as Serum Ascites Albumin Gradient (SAAG). This study aims to analyze the compatibility of SAAG and ascitic fluid evaluation to the clinical diagnosis of patients in Dr. Wahidin Sudirohusodo Hospital Makassar. The retrospective cross-sectional study was conducted by taking data from all patients with ascites condition examining both ascitic fluid and serum albumin simultaneously or within 3 days at the Dr. Wahidin Sudirohusodo Hospital Makassar from January – August 2018. The statistical analysis was performed for frequency distribution and Kappa statistical test to assess the compatibility of SAAG and ascitic fluid evaluation to clinical diagnosis of the patient. The study was conducted on 68 subjects and found that both ascitic fluid examination and SAAG were significantly compatible to the clinical diagnosis, 25.8% (p <0.05), 42.5% (p <0.001), respectively. SAAG and ascitic fluid evaluation were significantly in accordance with the clinical diagnosis of the patient. The compatibility value of SAAG is greater than ascitic fluid evaluation so that SAAG is more recommended for ascites examination.